The Effectiveness of Training Program to Develop the Social Competency of The Second Grade Basic Studemts With Learning Disabilities - Aya Amer Badraddin; Afrah Yasseen Dabagh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The aim of the research is to identify "the effectiveness of a training program to develop social competency of students in the second grade basic with learning disabilities" by verifying three zero hypotheses, and the two researchers followed the experimental approach, where the research sample was chosen from students of the second grade with Learning disabilities in the Daleen Private School in the Erbil Governorate Center for the academic year (2020-2021), and the number of the sample reached (14) students, and they were divided randomly into two groups, the first experimental group, the number of its members was (7) students, the second was a control, and the number of its members was (7) students. The two researchers chose the experimental design of two equal groups with the test (pre-post), and parity was performed for the two groups in each of the variables of chronological age, IQ, and social competence. The experimental group was taught with the proposed training program, and the control group was taught in the traditional way. The two researchers prepared the scale of social competency through an exploratory questionnaire and based on the scale (Merrill, 1993), which was previously expressed (Al-Zubaidi, 1995). The scale included (42) a paragraph describing the areas of social competency (personality, self-control, academic, emotional). The validity and reliability of the scale were verified before applying it to the two groups. The experiment (training program) was applied during the first semester of the academic year (2020-2021). The time of each session reached (45) minutes, three sessions per week, for a period of two (8) weeks. After collecting the data, it was analyzed and processed statistically. The results found that there was a statistically significant difference at a level of significance (0.05) between the mean scores of the experimental and control groups in social competency and in favor of the experimental group. Recommendations and proposals were presented according to the findings of the research.